Implementation of the Project Method in the Independent Curriculum as a Strategy to Improve Early Childhood Creativity - Syifauzakia, Syifauzakia; Rohaeni, Nani (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
Creativity is the ability to produce something new, valuable ideas, and solutions. In early childhood, creativity includes not only arts and crafts but also the ability to think critically, solve problems, and innovate in various situations. Creativity is an important aspect in children's development because it helps them to express themselves, improve cognitive abilities, and develop social-emotional skills. However, the lack of creative stimulation in early childhood is still a common problem. It is believed that the project method in the Independent Curriculum can be an effective strategy to improve the creativity of young children. The aim of this research is to determine the implementation of project method learning in the Independent Curriculum in Early Childhood Education as a strategy to increasing the creativity of early childhood. The research method in this study uses a qualitative descriptive approach with a literature study method where journal articles, books and e-books are used as reference material in writing. The data analysis used in this research is content analysis. The results obtained from this research indicate that the project method in the independent curriculum can be used as an effective strategy for improving children's creativity from an early age, in its implementation the teacher a very important role, while the implementation stages involve careful planning steps, flexible implementation of projects according to the topic, and assessment focuses on the process. The interesting project method, encouraging children to participate actively and responsibly. So that the resulting abilities show an increase in the ability to think creatively, imaginatively, problem solving, collaboratively and producing work.